Dampak Globalisasi terhadap Penerapan Hukum Perdata Islam di Indonesia - Daud, Sulhi M; Umar, Hasbi; Adawiyah, Robiatul (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine the influence of globalization on the application of Islamic civil law in Indonesia. The approach used is descriptive-analytical qualitative to explore the relationship between globalization and Islamic civil law. The research results found that adaptation of Islamic civil law requires public education strategies, use of information technology, women's empowerment, as well as collaboration between Islamic law and positive law.